Autism Spectrum Disorder and Epilepsy: Point of Convergence or Divergence - Valaparambil, Karthika Ajit; Sundaram, Soumya (International Journal of Epilepsy, 2025)
Autism spectrum disorder (ASD) is characterized by deficits in social communication and interaction in various contexts, along with restrictive and repetitive behaviors. Individuals with ASD often have cooccurring neurodevelopmental, neuropsychiatric, and neurological disorders. The prevalence of epilepsy in ASD ranges from 2 to 60%. The notable association between autism and epilepsy highlight the shared neurobiological features in both conditions that include synaptic dysfunction, abnormalities in cell signalling and proliferation, chromatin modification and transcription, and an imbalance between excitation and inhibition. Recent advances in next-generation sequencing techniques have revealed similar etiological and molecular mechanisms underlying autism and epilepsy through the identification of various genes linked to their pathophysiological processes. Older age, female sex, the presence of intellectual disability, developmental delay, and severe symptoms of autism are risk factors for epilepsy reported in autistic individuals. In this review, we will focus on the underlying molecular mechanisms, clinical characteristics, predictive factors for developing epilepsy in autism, and the common genetic disorders associated with the ASD-epilepsy phenotype.
Keywords: autism; epilepsy; autism spectrum disorder; genetic; pathophysiology; ASD-epilepsy phenotype